H5N1 Clade 2.3.4.4b Infections in Domestic Cats During an Avian Influenza Outbreak in Italy: Implications for One Health Surveillance - Giulia D'Annunzio; Ana Moreno; Giovanni Tosi; Patrizia Bassi; Alessio Bortolami; Giuseppe Diegoli; Alessandra Drago; Alice Fusaro; Luca Gelmini; Lucia Rita Gibelli; Tiziana Lazzarotto; Elisabetta Lilliu; et al. (Influenza and Other Respiratory Viruses, 2026)
ABSTRACT Background H5Nx goose/Guangdong (Gs/GD) lineage highly pathogenic avian influenza (HPAI) viruses pose a significant public health threat due to their global spread, mutation accumulation, and expanding host range. The descendant clade 2.3.4.4b has been causing widespread infections in birds and increasing spillover events in mammals. Methods This report documents the first fatal case of highly pathogenic avian influenza virus (HPAIV) H5N1 clade 2.3.4.4b infection in a domestic cat in Italy, detected in early January 2025. The cat (CAT 1) resided on a backyard poultry farm experiencing a high pathogenicity avian influenza outbreak and succumbed rapidly following the onset of respiratory signs. A second exposed cat (CAT 2) developed clinical disease without fatal outcome. Comprehensive outbreak investigations were conducted, including pathological, serological, molecular analyses, and genomic characterization. Results Pathological examination of CAT 1 revealed acute necrotizing bronchointerstitial pneumonia, non‐suppurative meningoencephalitis, and disseminated foci of hepatic necrosis. Interestingly, the PB2‐E627K mutation associated with mammalian virus adaptation was observed in the feline viral isolate compared to avian isolates. Such polymerase complex mutations are key determinants of host range and increase pathogenicity in mammals. CAT 2 from the same farm tested negative for AIV genome detection but subsequently seroconverted for antibodies against NPA, H5, and N1. Conclusion Sharing these findings is crucial for surveillance aimed at enabling early identification of increased risks to human and animal health, preventing cross‐species viral transmission and mitigating the risk of potential spillover events.